Pengaruh Teknik Relaksasi Nafas Dalam dan Kompres Hangat terhadap Penurunan Intensitas Nyeri Haid (Dismenore Primer) pada Remaja - Mulyani, Sindi Sri; Astuti, Retno Puji (MPI Press, 2024)
Background: Dysmenorrhea can be described as pain that occurs during menstruation due to excessive release of prostaglandins, causing hyperactivity of uterine contractions and resulting in pain during menstruation. Non-pharmacological measures to treat dysmenorrhea include deep breathing relaxation techniques and warm compresses.Objective: To identify the effect of deep breathing relaxation techniques and warm compresses on reducing the intensity of menstrual pain (primary dysmenorrhea) in adolescents.Method: This type of research is qualitative research with a case study. Sampling used purposive sampling. The sample for this research is Ms. N and Ms. C. The sample was divided into 2 groups, 1 was given deep breathing relaxation intervention and the other was given warm compresses. The data obtained was then compared using SOAP. Observations were carried out for 3 days. begins on the first day of menstruation. The research instrument used to collect data was by using a pain measurement observation sheet according to Smeltzer, S.C. Balre B.G. Results: The nalfals dalpalt dalpalt relaxation technique reduced the intensity of halid skalal scallal pain from the first visit to the 6th paldal skalal in the second visit, there was a decrease in the 4th paldal scallal pain intensity. Meanwhile, the halingalt paldal salalt scallal compress relaxation technique resulted in a decrease in the intensity of pain t the scale of pain from the first talmal visit paldal skallal 6 in the second visit there was a more significant reduction in the paldal skalal 2 remaljal of the daughter who was given the halngalt compress relaxation technique. Conclusion: It was found that there was a difference in reducing the intensity of pain in young women who were given the intervention of deep breathing relaxation techniques and warm compresses.